Screw placement in two different implants for proximal humeral fractures regarding regional differences in bone mineral density: An anatomical study. (September 2021) - Holweg, Patrick; Dauwe, Jan; Grechenig, Peter; Holter, Magdalena; Staresinic, Mario; Feigl, Georg; Bakota, Bore
Highlights: The aim of this study was to evaluate proximal humerus plating regarding screw length and over penetration. Trabecular BMD has a significant effect on the remaining bone stock after drilling to the far cortex. Future plates should adapt the distribution and the direction of the screw holes. Abstract: Background: The aim of this study was to investigate proximal humerus plating regarding drill depth and over penetration of the glenohumeral joint and to find a relation between these findings and different areas of bone mineral density (BMD) in the humeral head. Material & Methods: The study sample involved 45 upper extremities from human adult cadavers. Two different plates (HOFER; PHILOS) were applied to the proximal humerus. Each hole was drilled until the respective participant thought to have placed the drill bit subchondral. Next, penetration of the far cortex was conducted to determine the residual bone stock. Additionally, the point of screw penetration of the far cortex was identified for each hole of the plates and allocated to five regions with different bone mineral density as described by Tingart et al. Results: The screw penetration rate and the residual bone stock were compared within the 5 BMD regions. A significantly thicker residual bone stock was found at the central region (SD ± 13.1 mm) than in the anterior region (SD ± 9.5 mm) and in the posterior region (SD ± 8.5 mm). The anterior region revealed a significantly higher penetration rate than the posterior region ( p = 0.01) and the central region ( p = 0.03). Conclusion: The anterior region of the humeral head was associated with a higher over penetration rate of the far cortex into the glenohumeral joint and a decreased bone stock after subchondral drilling representing a reduced bone mineral density (BMD). Level of evidence: Cadaver Study